2020
DOI: 10.1071/rdv32n2ab220
|View full text |Cite
|
Sign up to set email alerts
|

220 Exploring the use of mesenchymal stem cells for treatment of mastitis and metritis in cattle

Abstract: The present study was carried out to isolate mesenchymal stem cells (MSCs) from adipose tissue of cattle (Bos indicus), characterise them, and apply them for the treatment of mastitis and metritis in the cow. Cattle MSCs were isolated from adipose tissue near the loin region of cow. Isolated adipose tissue was subjected to enzymatic digestion using 2% collagenase with agitation at regular intervals. The cells obtained after digestion were resuspended in cell culture flasks containing growth enriched medium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Conflicting results, however, exist regarding the efficacy of prepartum immunization against uterine pathogens in reducing the incidence of metritis in dairy cows; hence, the uterine protective role of adaptive immunity has not been completely established [64]. Nonetheless, to reduce uterine pathogens associated with the occurrence of metritis, new promising results have been reported by Singh and coworkers [80] in a recent study that indicated the potential use of mesenchymal stem cells (MSc) from the adipose tissue of cattle (Bos indicus) for the treatment of metritis through wound healing and also decreasing microbial infection.…”
Section: Metritismentioning
confidence: 99%
“…Conflicting results, however, exist regarding the efficacy of prepartum immunization against uterine pathogens in reducing the incidence of metritis in dairy cows; hence, the uterine protective role of adaptive immunity has not been completely established [64]. Nonetheless, to reduce uterine pathogens associated with the occurrence of metritis, new promising results have been reported by Singh and coworkers [80] in a recent study that indicated the potential use of mesenchymal stem cells (MSc) from the adipose tissue of cattle (Bos indicus) for the treatment of metritis through wound healing and also decreasing microbial infection.…”
Section: Metritismentioning
confidence: 99%
“…The adoption of mesenchymal stem cells (MSc) rather than epithelial and myoepithelial progenitor cells, on the other hand, is promising. Recent studies have found that mesenchymal stem cells derived from bovine adipose tissue have an additional therapeutic benefit, MSc could be used to treat mastitis in cattle by promoting wound healing and reducing microbial infection [117]. The antinflammatory, antibacterial, and immunomodulatory activities of MSc are linked to their activation of innate immunity [118], MSc boost the expression of the bBD4A and NK1 genes, which code for antibacterial peptides (APs) such as cathelicidin, indolamine 2,3-dioxygenase, and hepcidin, all of which have broad-spectrum bacteriostatic and bactericidal capabilities [119].…”
Section: Mammary Stem Cellsmentioning
confidence: 99%